Analysis of PSAK 109 Zakat Accounting Standard Statements at Al-Washliyah Amil Zakat Institutions - Khoirunnisa Ritonga; Yenni Samri Juliaty Nasution (Journal of Indonesian Management, 2022)
The purpose of this research is to understand that zakat bookkeeping at LAZ WASHAL North Sumatra is in accordance with PSAK No. 109. This study was conducted to determine the application of accounts made by LAZWASHAL in North Sumatra and Zakh in Shadaqah. Infaq based on PSAK No.109 concerning Zakat Reconciliation. The method used is descriptive and the type of data is qualitative. The results of this research state that LAZ WASHAL North Sumatra does not use PSAK109. When submitting the annual report. PSAK No. 109 functions to adjust the accounting for zakat infaq/shadaqah, accounting and disclosure of zakat transactions, approaches and measurements.